ECK-Secure Authenticated Key Exchange against Auxiliary Input Leakage. (8th May 2021) - Li, Sujuan; Zhang, Futai
Abstract: Authenticated key exchange protocols are quite important primitives for practical applications, since they enable two parties to generate a shared high entropy secret key. In this paper we mainly focus on the authenticated key exchange (AKE) against auxiliary input leakage. As the major contribution of this work, we present a generic framework for the construction of AKE protocols that are secure against auxiliary input leakage. An instantiation based on the generalized decisional Diffie-Hellman (GDDH) assumption in the standard model is also given to demonstrate the feasibility of our proposed framework. We also give a comparison among the existing leakage resilient AKE protocols with auxiliary inputs.